Shale gas : ecology, politics, economy - Zhiltsov, Sergey Sergeevich (Handbook of environmental chemistry, 2017)
This book highlights various aspects of shale gas production and discusses the associated problems, which have greatly influenced the current situation on the global gas market. It focuses on issues such as production technologies, environmental protection, and the impacts of shale gas production on human beings. Further, it investigates the role of shale gas in the development and implementation of foreign policy of many nations that welcomed the possibility to produce this hydrocarbon in their own countries. Taking into consideration the information published by world energy research centers, the prospects of shale gas production in different regions of the world are examined in detail. Given its coverage and scope, the book will greatly benefit specialists in the areas of hydrocarbon production, international relations and foreign policy, world economics and technologies, ecology and environmental protection.